Cloud-Based DDoS HTTP Attack Detection Using Covariance Matrix Approach - Abdulaziz Aborujilah; Shahrulniza Musa (Journal of Computer Networks and Communications)
In this era of technology, cloud computing technology has become essential part of the IT services used the daily life. In this regard, website hosting services are gradually moving to the cloud. This adds new valued feature to the cloud-based websites and at the same time introduces new threats for such services. DDoS attack is one such serious threat. Covariance matrix approach is used in this article to detect such attacks. The results were encouraging, according to confusion matrix and ROC descriptors.